Spatial unification of coupling interactions between EGFR and PTPs establishes a growth factor sensing network - Stanoev, Angel (Technische Universität Dortmund, 2018)
Cells continuously sense and respond to stimuli from the non-stationary environment. For this, they optimise processing of the perceived signals while maintaining continuous responsiveness. Cell surface receptors, such as the receptor tyrosine kinases, comprise the first layer of sensing. They translate the extracellular signal into internal activity using the protein interaction networks in which they are embedded. The proto-oncogenic epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase whose sensitivity to epidermal growth factor (EGF) and signalling duration determines cellular behaviour. In the canonical view, signal processing occurs through the ligand-induced dimer formation mechanism and subsequent trans-phosphorylation. However, it has been also established recently that signal amplification via the unliganded EGFR monomers through an autocatalytic mechanism enhances the phosphorylation response of EGFR. In this thesis, I demonstrate how autocatalytic phosphorylation of EGFR in concert with the coupling interactions with the protein tyrosine phosphatases (PTPs) shape the response dynamics of EGFR. Single cell dose-response analysis revealed that a toggle switch between autocatalytically activated monomeric EGFR and the tumour suppressor PTPRG at the plasma membrane (PM) shapes the sensitivity of EGFR to EGF dose. As the system exhibits switch-like activation due to the bistable regime of operation, irreversible activation occurs as an adversary side effect. To ensure continuous growth factor sensing, the system is positioned outside of the bistable regime by the PM-localised PTPRJ, which negatively regulates EGFR phosphorylation. On the other hand, a spatially-distributed negative feedback with the ER-bound PTPN2 that is established by vesicular trafficking resets the phosphorylation state of monomeric EGFR on the plasma membrane. The distinct recycling route of the unliganded receptor, as opposed to the unidirectional degradation route towards the perinuclear area of the liganded receptor, enables it to repopulate the plasma membrane and thus maintain sensitivity to upcoming stimuli. In this manner, the coupling interactions between EGFR and the PTPs on different membranes are spatially unified in a network that enables sensing of time-varying EGF signals. The signal processing capabilities of this network are optimised by the system organisation, as its parameters are poised at the criticality point, just outside the bistable regime of operation. In this region, the EGFR response is characterised by prolonged but reversible phosphorylation, enabling the cell to maintain a balance between preserving a transient memory of previous EGF stimulations, while still remaining responsive to upcoming stimuli.
Keywords: Growth factor sensing; Signalling networks; Dynamical systems; Criticality; Autocatalysis; Vesicular trafficking; Spatial-temporal dynamics; Functional imaging; Epidermal growth factor receptor; Protein tyrosine phosphatases; 570; Wachstumsfaktor; Zellbiologie